Root Submergence Technique: Forgotten Terrain Revisited - Shrestha, Rejina; Pradhan, Shaili; Gorkhali, Ranjita Shrestha; Verma, Anand (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
The resorption of the alveolar ridge is an inevitable phenomenon after tooth extraction and continues throughout the lifespan of an individual. Socket preservation, hard and soft tissue augmentation procedures are indicated to compensate alveolar bone resorption. Compensation can also be done by masking with acrylic flanges, pink porcelain and gingival veneers. However, procedures to preserve the bone anticipatory to the loss after extraction should be prioritised. This paper reports a case of fractured non-vital tooth where root submergence technique was done. A follow-up at 6 months presents intact bone aiding in the aesthetics and function of the prosthesis.